Efectos anticontaminantes de concentraciones de aceites esenciales de orégano y romero en queso fresco no pasteurizado - Rivas Vera, Luis Andrés (2024)
The research aimed to evaluate the anti-pollution effect of concentrations of oregano and rosemary essential oils used as edible coatings on unpasteurized cheese. The factors studied were: essential oil (oregano and rosemary) and concentration (0.5%, 1% and 1.5%). A Completely Randomized Design (CRB) with a bifactorial AXB arrangement was applied resulting in six treatments plus a control, with three replicates per treatment, and an experimental unit of seven cheeses, each weighing 1000 g. The variables studied inclueded microbiological quality (total coliforms, Escherichia Coli, Staphylococcus aureus and Salmonella), shelf life and sensory acceptability. However sensory acceptability could not be evaluated due to the product's quality from the first day, which was outside the limit established by the INEN 1528 (2012) standard. It was determined that the coatings did not show a significant effect (p < 0.05) against total coliforms and Escherichia coli. In contrast, they did have a significant effect on Staphylococcus aureus, with treatment (7) standing out by presenting a lower quantity of CFU/g (6.2 X 10^3) and a shelf life of 7 days. Additionally, all treatments with coatings were free of Salmonella, unlike the control (without coating), which did present this bacteria. However, all treatments exhibited total coliforms and Escherichia coli from day one, exceeding the quality standards specified by the product regulations.